POSSIBILITIES OF DESIGNING VEHICLE DETAILS ON COMPUTER IN 3D FORMAT - Nizomiddinova Maftuna Shoirjonovna; Tursunova Muazzam Zokirjonovna (Western European Studies, 2024)
This article explores the possibilities of using computer 3D software tools in the process of car tuning and design. The article shows the processes of creation, analysis and optimization of car details with the help of computer-aided design, 3D model games and programs. With the help of 3D software tools, it is possible to analyze the design, material selection, aerodynamics and aeroloading of car details, conduct tests and present visions for consumers
Keywords: car design; computer graphics; car tuning